Facilitating Learning and Research Engagement of 4th year Undergraduate Students: the Outcomes of Student Self-Assessment Survey - Yoshida, Asako (Qualitative and Quantitative Methods in Libraries; Vol 4 No 4 (2015): December 2015 Issue, 2017)
Teaching faculty and a liaison librarian began exploring ways to facilitate undergraduate student engagement in research, in the context of a 4th year research seminar course.  The course was a long established course, ―Seminar in Foods and Nutrition,‖ in the Department of Human Nutritional Sciences, University of Manitoba, Canada.  The class was small, and eight students completed the course during the 2014 Winter semester.  The Research Skills Development Framework (RSD), which was developed at Adelaide University, Australia, was adopted as a conceptual model for collaboratively reorganizing and realigning learning and instructional activities.  The RSD framework was very useful in maintaining the shared interest among the collaborators in facilitating student learning.  An online survey with 19 Likert-scale questions was administered identically at the beginning and end of the course to measure student self-assessment of research skills.  The survey results showed that the efforts in supporting student learning paid off. There were positive learning outcomes in nine research skill areas, and two additional skill areas showed positive trends.  They are all corresponding to information literacy.